A REVIEW OF INTEGRATED MARKETING COMMUNICATIONS (International Journal of Food and Nutritional Sciences, 2022)
Purpose: To deliver a relevant and consistent message about the products to the target market, integrated marketing communication (IMC) plays an important role. Hence, this study aims to understand the concept of integrated marketing communication along with the challenges.Methodology: In order to understand and explain the nature of integrated marketing communications as well as the tools that marketers employ; this research employs a qualitative analysis.Findings: The integrated marketing communications play important role in reaching the consumers and help to convey a clear and consistent message to create a brand image. However, there are some challenges to deploy the integrated marketing communications.Practical implications: The concept of the integrated marketing communication along with the challenges are analysed from the extant literature. Originality/value: This article represents an overview of the integrated marketing communication for academics and practitioners to get the glimpse of the happenings in this incessantly evolving field.Conclusion: The integrated marketing communication is integral to reach to the customers and keep engaging the existing customers. Studies show that IMC helps in delivering a coherent message and increase brand equity.